2022
DOI: 10.3390/rs14236145
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Underestimation and Overestimation in PolInSAR Forest Canopy Height Estimation Using Microwave Penetration Depth

Abstract: PolInSAR is an active remote sensing technique that is widely used for forest canopy height estimation, with the random volume over ground (RVoG) model being the most classic and effective forest canopy height inversion approach. However, penetration of microwave energy into the forest often leads to a downward shift of the canopy phase center, which leads to model underestimation of the forest canopy height. In addition, in the case of sparse and low forests, the canopy height is overestimated, owing to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…sample points are located in areas with less forest cover in which the microwave penetra-tion is deeper and other conditions cause larger errors [36][37][38][39]. As shown by the results after masking these areas (Figure 18b), our proposed method is effective and can improve the forest canopy height estimation by overcoming the phase error.…”
Section: Discrete Sample Point Error Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…sample points are located in areas with less forest cover in which the microwave penetra-tion is deeper and other conditions cause larger errors [36][37][38][39]. As shown by the results after masking these areas (Figure 18b), our proposed method is effective and can improve the forest canopy height estimation by overcoming the phase error.…”
Section: Discrete Sample Point Error Analysismentioning
confidence: 84%
“…There is also slight underestimation at RH100 heights greater than 40 m, which may relate to the forest conditions, data conditions, and beamforming algorithms described previously; this effect may even relate to microwave penetration of the canopy, which we intend to further analyze in the next step of our study. In addition, there is also significant overestimation for a few sample points where RH100 is less than 20 m. We superimposed these sample points on Google Earth and found that almost all of these sample points are located in areas with less forest cover in which the microwave penetration is deeper and other conditions cause larger errors [36][37][38][39]. As shown by the results after masking these areas (Figure 18b), our proposed method is effective and can improve the forest canopy height estimation by overcoming the phase error.…”
Section: Discrete Sample Point Error Analysismentioning
confidence: 99%